AB1161 Portuguese adaptation and validation of the ankylosing spondylitis quality of life (ASQOL) questionnaire. (15th June 2017) - Άgueda, A; Heaney, A; McKenna, SP; Barcelos, A
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic rheumatic disease that affects mainly the axial skeleton and entheses. If left untreated, AS evolves with limited spine mobility and irreversible structural changes, with severe repercussions in patients' quality of life. Throughout the years many instruments have been used in order to evaluate AS impact in patients' lives, focusing predominantly on symptoms and functioning however, these instruments do not inform on the impact of the condition on quality of life (QoL). The ASQoL is a patient reported outcome measure, specifically developed to evaluate QoL in AS patients. It has been adapted to several languages worldwide, though a Portuguese version hadn't been developed yet. Objectives: Translation of the ASQoL questionnaire into Portuguese and ascertain its psychometric properties. Methods: Translation of the original UK English ASQoL into Portuguese was performed by bilingual panel and then assessed by a lay panel. Cognitive debriefing interviews were performed with AS patients to assess face and content validity. Finally, a sample of AS patients were included in a test-retest postal survey, administered on two different occasions, two weeks apart, to investigate the reliability and construct validity of the new Portuguese adaptation of the ASQoL. Nottingham Health Profile (NHP) was used as a comparator measure. Results: The Portuguese version of ASQoL proved to be relevant and easy to understand. Validation of the ASQoL included fifty-eight AS patients, with a mean age of 51 years (Range 25.0 – 80.0), with 55.2% males. The Portuguese ASQoL had good internal consistency at Time 1 (α =0.93) and Time 2 (α =0.91). Test-retest reliability was excellent, with a strong positive correlation between scores at two time points (r=0.92, p<0.001). Correlation between ASQoL scores and NHP was moderately strong with Spearman's rank correlation coefficients between ASQoL and NHP section scores, including the distress scale embedded within, all p<0.001. These results suggest that patient's quality of life is influenced by many factors in addition to disease severity, including social skills and ability to adapt to physical limitations. The Portuguese version of ASQoL was able to discriminate between patients who differed on their perception of general health and presence of comorbidity, although there were no significant differences according to self-perception of disease severity. Conclusions: The Portuguese version of the ASQoL performed well, demonstrating good psychometric properties for use in clinical studies and trials of patients with AS. The lack of significance in the analysis by self-perceived disease severity may be due to the relatively small sample size. References: LC Doward, A Spoorenberg, SA Cook, D Whalley, PS Helliwell, LJ Kay, SP McKenna, A Tennant, D Van der Heijde, MA Chamberlain; Development of the ASQoL: a quality of life instrument specific to ankylosing spondylitis; Ann Rheum Dis 2003;62:20–26. KL Haywood, AM Garratt, K Dziedzic, PT Dawes. Generic measures of health-related quality of life in ankylosing spondylitis: reliability, validity and responsiveness. Rheumatology 2002;41:1380–1387. Disclosure of Interest: None declared